A Contribution From the American-Indonesian Scholarship Program Alumni Association to Indonesia: The ’Local Heroes for Forest Protection’ Initiative in Southeast Sulawesi, West Papua, and East Nusa Tenggara - Hermudananto, Hermudananto; Alfian, Alfian; Lapau, Fitri; Rahayu, Kadek Ridoi; Sukoyo, Kuntari Sri; Zulkifli, Miranti Triana; Rajahasta, Patih; Murianty, Riana; Hermawan, Rudi; Landa, Silvia Anastasia (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
To minimize forestry sector greenhouse gas emissions by 2030, Indonesia needs stakeholder participation, especially youth. The AmericanIndonesian Scholarship Program Alumni Association (ALPHA-I) initiated the